Negative Control of RpoS Synthesis by the sRNA ReaL in Pseudomonas aeruginosa - Thi Bach Nguyen, Hue; Romero A., David; Amman, Fabian; Sorger-Domenigg, Theresa; Tata, Muralidhar; Sonnleitner, Elisabeth; Bläsi, Udo (Frontiers in Microbiology, 2018)
Pseudomonas aeruginosa (Pae) is an opportunistic human pathogen, able to resist host defense mechanisms and antibiotic treatment. In Pae, the master regulator of stress responses RpoS (σS) is involved in the regulation of quorum sensing and several virulence genes. Here, we report that the sRNA ReaL translationally silences rpoS mRNA, which results in a decrease of the RpoS levels. Our studies indicated that ReaL base-pairs with the Shine-Dalgarno region of rpoS mRNA. These studies are underlined by a highly similar transcription profile of a rpoS deletion mutant and a reaL over-expressing strain.